Franklin's Halloween - Bourgeois, Paulette; Clark, Brenda (New York : Scholastic Inc., 1996)
Franklin and his friends attend a Halloween party that features a mysterious ghost.
"RL: 2"--P. [4] of cover.
"004-007"--P. [4] of cover.
Keywords: Halloween -- Fiction; Turtles -- Fiction; Ghosts -- Fiction